The Impact of Internal Control and Management Control Systems on Financial Performance, with Operational Efficiency as a Mediating Variable: A Systematic Literature Review - Agusman Sianturi; Inten Meutia; Hasni Yusrianti; Ika Sasti Ferina; Yusnaini Yusnaini (Green Publisher Indonesia, 2026)
This study presents a Systematic Literature Review (SLR) examining the influence of internal control and management control system (MCS) on financial performance, with operational efficiency as a mediating variable. The review synthesizes 50 empirical articles published between 2020 and 2026, collected from SINTA, Emerald, Elsevier (ScienceDirect), MDPI, ProQuest, Taylor & Francis, and Google Scholar using defined inclusion–exclusion criteria. The findings indicate a growth trend in publications, with a peak in 2023, and reveal that most studies employ quantitative approaches grounded primarily in Agency Theory and Contingency Theory. Empirical evidence shows that internal control and MCS are the most frequently examined determinants of financial performance, while operational efficiency increasingly serves as a mediating mechanism linking control systems to profitability outcomes. Financial performance is predominantly measured using accounting-based indicators such as ROA and ROE. The synthesis highlights empirical inconsistencies and identifies gaps, particularly the limited integration of mediation models, cross-country analysis, and robust analytical methods. This review provides a structured overview of research trends and future research directions in management, control and financial performance literature.